Menelisik Unit Usaha Pertashop dalam Upaya Meningkatkan Pendapatan Asli Desa - Papin, Dekriano Musbiawan Dearan; Martiningsih, Rr. Sri Pancawati (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
The large number of Pertashop business units that are not running optimally has recently become an obstacle for Pertashop owners. The aim of this research is to analyze the development of the Pertashop business unit and the obstacles that trigger a decline in community interest and to see the ability of the Pertashop business unit at BUM Desa to increase the village’s original income. The research was conducted at BUM Desa Anyar in Anyar Village. This research uses qualitative methods with a descriptive analysis approach. The result of the research show that the Pertashop business unit in Anyar village has experienced a decline in sales volume since the increase in fuel prices has reduced the buying interest of the people of Anyar village. As a result, the Pertashop business unit in the new village has not been able to increase the village’s original income. The survival of the Pertashop business unit in the new village is due to (1) There are expectations from the public regarding their fuel comsumption patterns; (2) There is hope for the government regarding its policies related to prices; and (3) The amount of investment that has been spent to set up a Pertashop business.